Distribution and Enrichment Characteristics of Selenium in Soil and Crops in Luoyang City, Henan Province - SONG Yanbin; WANG Xikuan; XIA Yan; HOU Jinkai; ZHAO Rui (Yankuang ceshi, 2022)
BACKGROUND The analysis of selenium enrichment characteristics in various crops planted in a certain area and investigation and evaluation of selenium content in selenium fertilizer crops can provide a basis for the development of selenium-enriched characteristic agriculture. It is important to find out the influencing factors of selenium content in different crops for developing selenium-enriched agricultural products. OBJECTIVES To understand the distribution and enrichment characteristics of Se in soil and crops in Luoyang City. METHODS The selenium resources detailed investigation project area and other agricultural planting areas in Luoyang City, Henan Province were chosen as the research object. The selenium content of 22 kinds of crops and their root soil were measured by ICP-MS, and the selenium enrichment characteristics of different crops were studied. RESULTS The average value of soil selenium in the study area was close to the standard of selenium-enriched soil in Henan Province. The selenium-enriched sites in acidic soil, neutral soil, alkaline soil, and overall soil accounted for 28.61%, 43.72%, 41.99%, and 40.56%, respectively. According to the evaluation of selenium enrichment coefficient of various crops, the study area was suitable for the development of selenium-enriched beans, oil-bearing crops, wheat, millet, sweet potato and other characteristic crops and selenium-enriched traditional Chinese medicine Stachys floridana Schuttl.ex Benth, but not suitable for the development of selenium-enriched corn. The correlation of selenium content in different crops with soil selenium content and pH showed that soil selenium content was the decisive factor of selenium content in crops, followed by soil pH. CONCLUSIONS In order to promote the development of selenium-enriched agricultural products in the study area, selenium fertilizer can be applied to improve the selenium content of crops. Crops planted in low selenium background soil, especially fruits, are suitable for applying selenium fertilizer, while millet planted in high selenium background soil is not suitable for applying selenium fertilizer.